2012
DOI: 10.1161/hypertensionaha.112.192971
|View full text |Cite
|
Sign up to set email alerts
|

Gene Trapping Uncovers Sex-Specific Mechanisms for Upstream Stimulatory Factors 1 and 2 in Angiotensinogen Expression

Abstract: A single-nucleotide polymorphism (C/A) located within an E-box at the −20 position of the human angiotensinogen (AGT) promoter may regulate transcriptional activation through differential recruitment of the transcription factors Upstream Stimulatory Factor (USF) 1 and 2. To study the contribution of USF1 on AGT gene expression, mice carrying a (−20C) human AGT transgene were bred with mice harboring a USF1 gene trap allele designed to knock down USF1 expression. USF1 mRNA was reduced relative to controls in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…This pattern may be partially attributed to local differences in angiotensinogen production by adipocytes (Dusserre et al 2000;Van Harmelen et al 2000a, b), which is suppressed by miR-31 and/or miR-584 in C allele homozygotes but not in A allele carriers. Such sex-specific differences in angiotensinogen expression have been confirmed in the case of AGT promoter polymorphism -20 C/A (rs5050) when transgenic mice producing human AGT was used (Park et al 2012). Interestingly, these differences were also depot specific with differences between omental and perigenital fatty tissue.…”
Section: Discussionmentioning
confidence: 82%
“…This pattern may be partially attributed to local differences in angiotensinogen production by adipocytes (Dusserre et al 2000;Van Harmelen et al 2000a, b), which is suppressed by miR-31 and/or miR-584 in C allele homozygotes but not in A allele carriers. Such sex-specific differences in angiotensinogen expression have been confirmed in the case of AGT promoter polymorphism -20 C/A (rs5050) when transgenic mice producing human AGT was used (Park et al 2012). Interestingly, these differences were also depot specific with differences between omental and perigenital fatty tissue.…”
Section: Discussionmentioning
confidence: 82%
“…The functions of Dhx36 and Psmc6 with female‐ and male‐specific strain differences, respectively, have not yet been investigated in the brain. Usf1 , which showed female‐specific strain differences in adulthood, has been shown to regulate angiotensinogen expression with consequences in females only (Park et al ). Furthermore, polymorphisms in Usf1 have been associated with neuropathological lesions in Alzheimer's disease (Isotalo et al ).…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, we showed that AGT expression in many tissues was decreased in USF1-deficient mice. 16 …”
Section: Discussionmentioning
confidence: 99%
“…14 Both USF1 and USF2 are essential for AGT transcriptional regulation 15 , and gender-specific mechanisms are involved in their activity on AGT expression in vivo . 16 USF1 polymorphisms were reported to be associated with the level of AGT expression in human fat biopsies. 17 AGT expression in the renal medulla was reported to be higher in subjects carrying the −20C allele than the −20A.…”
Section: Introductionmentioning
confidence: 99%